Analysis of Decision-Making Styles of Department of Sports Management Students - Barbaros Serdar Erdoğan; Gökhan Acar (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to examine the decision-making styles of the students in the department of sports management. The population of the study comprises a total of 158 students (51 female, 107 male) randomly selected from the 1st, 2nd, 3rd and 4th year studentsof Mehmet Akif Ersoy University, Physical Educationand Sports Academy, Department of Sports Management inBurdur province in 2016 - 2017 academic year. The data obtained in the survey study were analyzed and evaluated with the help of SPSS 13.0 statistical program. Frequency (f) analysis was performed to represent the demographic information of students participating in the survey. The arithmetic mean and standard deviation values ​​were determined to identify the decision-making styles of the students. The mean of the answers given by the Department of Sports Management students to questions about avoidant decision-making style is at the level of "Sometimes True" . Based on this, it is concluded that when students make decisions, they sometimes act avoidant. The mean of the answers given by the students questions about dilatory decision-making style is at the level of "Sometimes True" Based on this, it can be said that students sometimes act dilatory when making decisions. The mean of the answers given by the students to questions about panic decision-making style is at the level of "Sometimes True". Based on this, students sometimes act panicked when making their decisions. A significant difference was detected between students living in the town and the students living in the provincial center in terms of panic decision-making. Based on this, the mean value of panic decision-making in students living in the town is significantly higher than the students living in the province center.